Brain activity and motor performance under different focus of attention in shooting of elite archer - an fNIRS study - Qin, K.; Wu, J.; Wang, S. (Journal of Human Sport & Exercise, 2025)
The correlation between different focuses of attention (FOAs) and performance in archery had been insufficiently explored. This study aimed to investigate brain activity under different FOAs, quantify the relationship between FOA and arrow scores in shooting. Sixteen elite archers were recruited to participate in this study. A 48-channel portable fNIRS device was used to collect hemodynamic signals in an outdoor environment. Each archer shot five arrows at a target placed 70 meters away. The results showed that motor performance at external and internal focus are not reach the statistical difference (t = 0.527, p = .606, Cohen`s d = 0.117). compared to IF, EF have lesser Delta-HbO in channel 14 (t = -2.218, p = .044, Cohen`s d = 0.640), channel 30 (t = -2.306, p = .042, Cohen`s d = 0.598) and channel 42 (t = -3.506, p = .005, Cohen`s d = 1.012), but have greater Delta-HbO in channel 37 (t = 2.638, p = .023, Cohen`s d = 0.762), channel 38 (t = 2.631, p = .023, Cohen`s d = 0.759). Additionally, compared to IF, EF have greater neural efficiency in channel 28 (p = .026). Compared to IF, EF enhanced activity in the visual cortex, particularly in V2 and V3, while decreasing activity in M1, S1, PMC, and SMA. Additionally, EF demonstrated greater neural efficiency in PMC and SMA. However, under IF, archers allocated additional resources to PMC and SMA to maintain performance levels comparable to those under EF.